A "Homo Shopiens" a buddhista filozófia tükrében - Bialkó, László (Kultúratudományi Szemle, 2024)
"Homo shopiens" in the light of Buddhist philosophy In this paper, I respond to András Gelencsér's book entitled Ábrándok bűvöletében, especially to the sub-chapter Homo shopiens. In this part, Gelencsér states that capitalism has turned people in developed countries into "perfect consumer machines" during the 20th century, which may have the consequence of ending modern civilisation. In my view, we have the possibility to change this, and I present Buddhist economics and philosophy as an alternative. The system what Gelencsér calls "turbo-capitalism" is based on desire. The Buddhist tradition holds that desire is the cause of our suffering. In other words, in order to live a truly happy life, we have to moderate our desires; we have to moderate our consumption. In this way we can avoid ending modern civilisation.